The Emerging Epidemiology of VRE in Canada: Results of the CNISP Passive Reporting Network, 1994 to 1998 - John M Conly; Marianna Ofner-Agostini; Shirley Paton; Lynn Johnston; Michael Mulvey; Amar Kureishi; Lindsay Nicolle; Anne Matlow; the Canadian Hospital Epidemiology Committee; the Canadian Nosocomial Infection Surveillance Program (Canadian Journal of Infectious Diseases)
OBJECTIVE: To provide a rapid and efficient means of collecting descriptive epidemiological data on occurrences of vancomycin-resistant enterococcus (VRE) in Canada.